Vegetation on expansive clays from Madrid and La Sagra region (Madrid-Toledo, Spain) - Luengo, Enrique; Magaña Ugarte, Rosina; Martínez Labarga, Juan Manuel; de Pablo Sanz, Rubén; Sánchez-Mata, Daniel (Mediterranean Botany, 2024)
Soils rich in expansive clays (i.e., smectite and montmorillonite, and, to a lesser extent, soft clays such as sepiolite and palygorskite) are found in a broad stretch running NNE-SSW from the east of Madrid to the Tagus River surroundings in the province of Toledo. These clays tend to give rise to a specific type of soil, known as “vertisols” or related argillic soils with vertic behaviour, varied chemical and sedimentological composition, and occasionally siliceous or dolomitic clasts. In these soils, where there is an absence of woody vegetation, the colonising nitrophilous vegetation becomes of particular interest through the usage and alteration of the land. These argillic soil plant communities are incredibly diverse, with flora suited to the unique hydrogeochemical conditions of these settings. The variety of these plant communities is determined by factors such as land use, lithology, terrain, and the level of humidity they can withstand. In the present work, we identified the primary plant community on the Madrid-Toledo expansive clays, as well as provide a preliminary approach to the different varieties and transitions to other related plant communities. The main dynamic and catena links are established, and a floristically summarised table is provided, along with a descriptive examination of the community’s behaviour and variability. Lastly, its conservation status and the high degree of threat to which it is subjected are assessed.